2013
DOI: 10.1002/2013gl058132
|View full text |Cite
|
Sign up to set email alerts
|

Sudden deep gas eruption nearby Rome's airport of Fiumicino

Abstract: On 24 August 2013 a sudden gas eruption from the ground occurred in the Tiber river delta, nearby Rome's international airport of Fiumicino. We assessed that this gas, analogous to other minor vents in the area, is dominantly composed of deep, partially mantle‐derived CO2, as in the geothermal gas of the surrounding Roman Comagmatic Province. Increased amounts of thermogenic CH4 are likely sourced from Meso‐Cenozoic petroleum systems, overlying the deep magmatic fluids. We hypothesize that the intersection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
3

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 22 publications
(50 reference statements)
3
23
3
Order By: Relevance
“…The δ 13 C CO2 of the offshore and CdM gases (− 1.7 to − 1.2‰ vs. PDB) is similar to other CO 2 -dominated gas manifestations of the area and interpreted by many authors as due to mantle/magma degassing and/or limestone thermometamorphism (see Introduction). In contrast to Ciotoli et al (2013), who suggested that CdM methane has a dominant thermogenic component, we think that methane at CdM, as well as at Canale Vignole site, is the result of a mixing, in different proportions, between: 1) abiogenic methane released from geothermal and volcanichydrothermal reservoirs (Tassi et al, 2012) and similar to that discharged at Palidoro; and 2) microbially produced methane similar to the offshore gas.…”
Section: Geochemical Characteristics and Origin Of The Emitted Gasescontrasting
confidence: 83%
See 2 more Smart Citations
“…The δ 13 C CO2 of the offshore and CdM gases (− 1.7 to − 1.2‰ vs. PDB) is similar to other CO 2 -dominated gas manifestations of the area and interpreted by many authors as due to mantle/magma degassing and/or limestone thermometamorphism (see Introduction). In contrast to Ciotoli et al (2013), who suggested that CdM methane has a dominant thermogenic component, we think that methane at CdM, as well as at Canale Vignole site, is the result of a mixing, in different proportions, between: 1) abiogenic methane released from geothermal and volcanichydrothermal reservoirs (Tassi et al, 2012) and similar to that discharged at Palidoro; and 2) microbially produced methane similar to the offshore gas.…”
Section: Geochemical Characteristics and Origin Of The Emitted Gasescontrasting
confidence: 83%
“…The isotopic data of CdM methane (δ 13 C CH4 −46.2 to −51.5‰ vs. PDB; δD CH4 −184.7 to −202‰ vs. SMOW) (Fig. 9) are similar to those published by Ciotoli et al (2013).…”
Section: Geochemical Characteristics and Origin Of The Emitted Gasessupporting
confidence: 78%
See 1 more Smart Citation
“…Moreover, the area has been subject to a complex and long-lasting interaction of geomorphic factors [30], and also characterised by the presence of two Quaternary volcanoes (e.g. Mts Sabatini and Alban Hills) responsible of surface manifestations of CO 2 -rich gas [24,32]. The town of Ostia was powered by wells, but also pressurized water was supplied, as we can argue from the external evidences (fistulae, traces inside buildings along Decumano).…”
Section: Site Descriptionmentioning
confidence: 99%
“…Moreover, in the last years, accidental gas blowouts have occurred during shallow well drillings in the western sector of the volcano, showing the presence of gas-pressurized aquifers confi ned under shallow impermeable horizons (Barberi et al, 2007;Ciotoli et al, 2013;Sella et al, 2014). The hydrothermal processes discussed in this paper after the study of a fossil system in the Zolforata di Pomezia area (Fig.…”
Section: Cap Rock Progressive and Cyclic Formation And Hydrothermal Hmentioning
confidence: 79%